Controllable synthesis and microwave absorption properties of Fe3O4@f-GNPs nanocomposites. (August 2020) - Jiang, Shan; Qian, Kun; Yu, Kejing; Zhou, Hongfu; Weng, Yunxuan; Zhang, Zhongwei
Abstract: The development of high efficiency electromagnetic wave absorbing material is beneficial to eliminate secondary microwave pollution caused by strong reflection of electromagnetic shielding material. In this paper, we report a facile solvothermal method for preparing a magnetic Fe3 O4 @ functionalized graphene nanoplates (f-GNPs) hybrid material by assembling spherical Fe3 O4 particles with integrity crystal on the surface of graphene sheet. The experimental results revealed Fe3 O4 @f-GNPs composites had better wave absorption performance than dielectric f-GNPs or magnetic Fe3 O4 because of impedance matching ability. Electromagnetic parameters and wave absorbing properties can be controlled by regulating the particle diameter. Fe3 O4 @f-GNPs composites dominate their good microwave absorbing performances including the minimum reflection loss (RL) value of −25 dB at a frequency of 10 GHz with a sample thickness of 2 mm and an effective absorption bandwidth of 2.4 GHz (below −10 dB). Moreover, The Fe3 O4 @f-GNPs with 232 nm Fe3 O4 exhibited shielding efficiency properties in the X band. Its absorption efficiency and total efficiency were about 32 dB and 25 dB, respectively. The nanohybrids are very promising for improving and expanding the application of the high-performance microwave absorption materials. Highlights: A magnetic Fe3O4@ functionalized graphene nanoplates (f-GNPs) hybrid material with controlled size was prepared. The reaction temperature has the greatest influence on the synthesis and distribution of hybrid particles. The Fe3O4@f-GNPs exhibited good wave absorption performance in the X band because of impedance matching ability. Electromagnetic parameters and wave absorbing properties can be controlled by regulating the particle diameter. Wave absorbing properties in different diameter range rises with the increase of particle diameter.